The place of Pierre Bourdieu's theories in (popular) cultural studies (BRAC University Journal, 2026)
This article examines the relevance of French sociologist Pierre Bourdieu’s theories to cultural studies. His key concepts such as cultural capital, habitus, field and symbolic violence are introduced and explained in relation to their prospects and limitations in the study of culture. We will argue that Bourdieu, though from a different vantage point than the key theoretical figures of cultural studies such as Raymond Williams, questions the hierarchy of cultural productions and consumptions. Importantly, his persistent argument that cultural productions (paintings, music and theatres) accrue their symbolic and social value mainly through the social status of the users is fundamental to how he challenges the hierarchy of the traditional notion of “high”, “low”, “elite” and “mass” cultures. Thus, “culture” for him is inherently a site of constant social struggle for change which perhaps is the key theoretical argument of cultural studies as an academic discipline. While this “bridge” between culture and society makes Bourdieu theoretically important in the field of cultural studies, we will further argue the methodological significance of Bourdieu’s own work of studying people’s “taste” empirically in his key tract La Distinction (1984). Since cultural studies as a discipline has an enduring interest in the everyday life of people belonging to different social groups in the forms of studies about their food habits, spatial positions, and medium of leisure in particular in the urban contexts, Bourdieu’s theories, when used adaptively, can be particularly insightful. We will conclude this paper by examining why Bourdieu will be useful in cultural studies in the 21st century’s urban Bangladesh defined by both the expansion of city lives and the “new middle class”.